Hydrogen bonding improved atom transfer radical polymerization of methyl methacrylate with a glycerol/1, 3‐dimethyl‐2‐imidazolidinone green system. Issue 3 (27th October 2017) - Tian, Mengying; Wang, Jirong; Zhou, Jun; Han, Jianyu; Du, Feipeng; Xue, Zhigang
ABSTRACT: 1, 3‐Dimethyl‐2‐imidazolidinone (DMI) was used as an efficient media in iron‐catalyzed atom transfer radical polymerizations (ATRPs) and AGET ATRPs of MMA. Both of these systems presented relatively high reaction rate and well controllability even in the presence of limited amount of DMI. In iron‐catalyzed AGET ATRPs, a variety of alcohols were served as reducing agents and all the polymerizations behaved excellent activity features, especially for glycerol. The hydrogen‐bond interaction between DMI and glycerol was also studied, which may release the reducing ability of glycerol by decreasing the viscosity of glycerol similar to deep eutectic solvents (DESs). © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 282–289 Abstract : This article reports the iron‐catalyzed "green" ATRP with DMI as ligand, and the hydrogen‐bond interaction between DMI and glycerol was also studied in detail, which increased the polymerization rate and controllability of the whole reaction process.